Market Imperfections, Capital Market Equilibrium and Corporation Finance - Stapleton, R. C.; Subrahmanyam, M. G. (Journal of Finance, 1977)
R. C. Stapleton, M. G. Subrahmanyam, Market Imperfections, Capital Market Equilibrium and Corporation Finance, The Journal of Finance, Vol. 32, No. 2, Papers and Proceedings of the Thirty-Fifth Annual Meeting of the American Finance Association, Atlantic City, New Jersey, September 16-18, 1976 (May, 1977), pp. 307-319